Optimalisasi Emisi Karbon Pada Pembangunan Rumah Sederhana Metode Risha - Fauziyya, Khansa Rafa; Lendra, Lendra; Uda, Subrata Aditama Kittir Aidon (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
Due to a series of natural disasters in Indonesia, swift rehabilitation and reconstruction efforts are necessary to repair homes and facilities with earthquake-resistant buildings. In response to this need, the Ministry of Public Works and Housing has developed the Rumah Instan Sederhana Sehat (RISHA) construction, which can be built quickly and is claimed to be environmentally friendly. The RISHA method is expected to reduce carbon emissions generated from the construction process. The choice of building materials plays a crucial role in construction, as the production of these materials requires significant energy and generates carbon dioxide (CO2). Selecting environmentally friendly materials can reduce energy consumption and carbon emissions throughout the building's lifecycle. This study aims to calculate the carbon emissions generated from the construction of houses using the RISHA method. The calculation method uses coefficients from The Inventory of Carbon and Energy (ICE) at Bath University. The study results show that one unit of RISHA house produces a total carbon emission of 18,392.34 KgCO2, with reinforced concrete, lightweight bricks, and cement being the main contributors. Optimization was carried out by replacing the original wall material of lightweight bricks with concrete blocks and the original floor covering material of ceramics with wooden parquet. The result was a 5.49% reduction in carbon emissions, amounting to 17,382.15 KgCO2.